Transformation of Selected Antibiotics and Dissolved Organic Matter under Simulated Sunlight - Niu, Xi-Zhi (Curtin University, 2018)
This dissertation presents the phototransformation of selected antibiotics (fluoroquinolone and sulphonamide) and dissolved natural organic matter in sunlit waters under controlled laboratory experimental conditions. It contributes to a better understanding of the photochemical fate of these antibiotics in the aquatic environment, the transient nature of fluoroquinolones, characterisation of dissolved organic matter and its chemical transformation under sunlight irradiation. The results of this work have significant implications for water quality and biogeochemistry of aquatic systems.